Improving students’ ability in reading comprehension by using herringbone technique - Simbolon, Putri Amelia; Sinurat, Bloner; E. Silalahi, Dumaris (Institute of Education and Social Research, 2023)
The goal of this research is to find out if herringbone technique significantly affects to the tenth-grade students in comprehending recount text at SMA Swasta Kampus Nommensen Pematangsiantar. This research is quantitative research with quasi experimental research design. The sample of for this research is taken from two classes namely experimental class (X-3) consist of 30 students that used herringbone technique and control class (X-2) consist of 30 students that used conventional technique selected by purposive sampling. The instruments for collecting data is reading comprehension test. The test is divided into two parts, namely the pre-test and the post-test, which are given to each sample. The researcher finds the total mean score of post-test in experimental group is 79,45 and the total mean score post-test in the control group is 72,22. After calculating the data from all points, the t-test score is 2,120. Then, the researcher consulted the value on the t-table, which has a significance of 5% and the value is 1,672. Therefore, the researcher finds that t-test is higher than the t-table (2,120 > 1,672). It can be concluded that Ha is accepted while Ho is rejected. The use of Herringbone Technique is significantly affect to the tenth-grade students in comprehending recount text at SMA Swasta Kampus Nommensen Pematangsiantar. Herringbone technique helps students to improve reading comprehension in developing main idea and finding detail information from the text.